A Pilot Study of an In-Home Multicomponent Exergame Training for Older Adults: Feasibility, Usability and Pre-Post Evaluation - Adcock, Manuela; Thalmann, Melanie; Schättin, Alexandra; Gennaro, Federico; de Bruin, Eling D. (Frontiers in Aging Neuroscience, 2019)
Aging is associated with sensory, motor and cognitive impairments that may lead to reduced daily life functioning including gait disturbances, falls, injuries and mobility restrictions. A strong need exists for implementing effective evidence-based interventions for healthy aging. Therefore, the aim of this study was to (i) evaluate the feasibility and usability of an in-home multicomponent exergame training and (ii) explore its effects on physical functions, cognition and cortical activity. Twenty-one healthy and independently living older adults were included (11 female, 74.4 ± 7.0 years, range: 65–92 years) and performed 24 trainings sessions (each 40 min) over eight weeks. The first part was conducted in a living lab (home-like laboratory environment), the second part at participants’ home. The multicomponent exergame included Tai Chi-inspired exercises, dance movements and step-based cognitive games to train strength, balance and cognition. Attendance and attrition rates were calculated and safety during training was evaluated to determine feasibility. Participants rated the usability of the exergame (System Usability Scale) and reported on their game experience (Game Experience Questionnaire). Physical and cognitive functions and cortical activity (resting state electroencephalopathy) were assessed pre and post intervention. Results showed a high training attendance rate for the living lab and the home-based setting (91.7 and 91.0%, respectively) with a rather high attrition rate (28.6%, six drop-outs). Half of the drop-out reasons were related to personal or health issues. System usability was rated acceptable with a mean score of 70.6/100. Affective game experience was rated favorable. Significant improvements were found for minimal toe clearance, short-term attentional span, and information processing speed (p < 0.05). No significant pre-post differences were found for cortical activity. To summarize, the exergame is generally feasible and usable for healthy older adults applied in an in-home setting and provides an overall positive emotional game experience. Nevertheless, flawless technical functionality should be a mandatory consideration. Additionally, the training might have potential positive influence on specific functions in older adults. However, the efficacy has to be evaluated in a future randomized controlled trial assessing the behavioral and neuroplastic changes in a larger population after a longer training period.